Substrate Binding Analysis of the 23S rRNA Methyltransferase RrmJ - Hager, Jutta (American Society for Microbiology, 2004)
The 23S rRNA methyltransferase RrmJ (FtsJ) is responsible for the 2′-O methylation of the universally conserved U2552 in the A loop of 23S rRNA. This 23S rRNA modification appears to be critical for ribosome stability, because the absence of functional RrmJ causes the cellular accumulation of the individual ribosomal subunits at the expense of the functional 70S ribosomes. To gain insight into the mechanism of substrate recognition for RrmJ, we performed extensive site-directed mutagenesis of the residues conserved in RrmJ and characterized the mutant proteins both in vivo and in vitro. We identified a positively charged, highly conserved ridge in RrmJ that appears to play a significant role in 23S rRNA binding and methylation. We provide a structural model of how the A loop of the 23S rRNA binds to RrmJ. Based on these modeling studies and the structure of the 50S ribosome, we propose a two-step model where the A loop undocks from the tightly packed 50S ribosomal subunit, allowing RrmJ to gain access to the substrate nucleotide U2552, and where U2552 undergoes base flipping, allowing the enzyme to methylate the 2′-O position of the ribose.